ANALYSIS OF THE LEVEL OF ENVIRONMENTAL LITERACY ABILITY IN STUDENTS AND STUDENTS AT MADRASAH ALIYAH SMIP 1946 BANJARMASIN - Sasmita, Ghina Naufal Atikah; Arisanty, Deasy; Angriani, Parida; Alviawati, Eva; Muhaimin, Muhammad; Hastuti, Karunia Puji (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Lambung Mangkurat, 2023)
The environment is the residence of living things in carrying out their life activities, in human activities that are not normal to meet the needs of life will have a negative impact on the environment, environmental pollution is one of the impacts. Environmental Literacy is one of the strong relationships between the community and their environment today, seen from how people live together, with each other with every part of their environment wherever everyone is different to act well in their routine activities by using their understanding of the conditions around their homes. The application of the Adiwiyata program in the world of education is because in the world of education it is easier to learn and apply various sciences, norms and ethics in an effort to achieve development goals, one of the rational alternatives to integrate environmental education. The implementation of the Adiwiyata program at MA SMIP 1946 for 2 years still shows the reality that is running improperly. There are several things that become obstacles in the implementation of the Adiwiyata program at MA SMIP 1946. This study was conducted to obtain in-depth data and information about the level of environmental literacy ability of students in MA SMIP 1946. This study is quantitative descriptive and uses percentage averaging analysis to measure the level of environmental literacy ability. The level of environmental literacy ability of MA SMIP 1946 students is included in the very high category, namely with an average score percentage score of 86%. Students have the basics of ecological knowledge, have a sense of care and willingness to act and are able to apply their knowledge to plan appropriate actions in solving environmental problems.